A 2600-year high-resolution climate record from Lake Trichonida (SW Greece) - Seguin, Joana; Avramidis, Pavlos; Dörfler, Walter; Emmanouilidis, Alexandros; Unkel, Ingmar (Quaternary science journal, 2020)
This paper aims at reconstructing the palaeoclimatic changes during the last 2600 years in southern Greece based on a proxy record from Lake Trichonida. For the first time, we provide a reliable age-depth model and continuous geochemical data for the largest and deepest lake in Greece. We use X-ray fluorescence (XRF) geochemical data supported by discrete mineral analysis based on X-ray diffraction (XRD), grain size distribution, and organic matter content to investigate changes in the lake sedimentary system and identify the major forcing mechanisms. A principal component analysis based on the XRF geochemical composition identifies the variation between carbonate-rich material, precipitating predominantly under drier and/or warmer conditions, and terrigenous sediment input, with it being more prominent during wetter and/or colder conditions. The first principal component (PC1) shows a very strong correlation with the weathering proxy log (Rb∕Sr), and we interpret both proxies as depicting fluctuations in the hydrological conditions. A cluster analysis, conducted on the continuous geochemical and colour parameters, highlights the similarities in the sediment characteristics deposited during wetter phases, notably during 1850-1750, 1500-1400, ca. 1100, and ca. 100 cal BP. - - When comparing the PC1 Trichonida record to independent records from the Balkans, we find generally concurring patterns on a multi-decadal to centennial scale. We show that phases with wetter conditions at Lake Trichonida coincide with a more negative North Atlantic Oscillation (NAO) index, suggesting that the precipitation variability in southern Greece is linked to changes in the NAO atmospheric pattern, as one major driving force. The 2600-year-long sedimentary record of Lake Trichonida contributes to a better understanding of Late Holocene palaeohydrological changes in an important climatic transitional zone in the eastern Mediterranean.
Gesehen am 17.02.2025